2015
DOI: 10.1021/acs.macromol.5b02360
|View full text |Cite
|
Sign up to set email alerts
|

Nearly Ideal Polymer Network Ion Gel Prepared in pH-Buffering Ionic Liquid

Abstract: We report a high-toughness ion gel with a nearly ideal polymer network prepared in an imidazoliumbased aprotic ionic liquid (aIL) with a controlled solution pH. We formed the ion gel from tetra-armed poly(ethylene glycol) (TetraPEG), i.e., an A−B-type cross-end coupling reaction of two different TetraPEG prepolymers. To complete this A−Btype reaction, we needed to optimize the reaction rate such that the two TetraPEGs were mixed homogeneously, which strongly depends on the pH or [H + ] in the aIL solution. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 61 publications
1
51
0
Order By: Relevance
“…1a). These ideal covalent polymer networks not only provide powerful tools to study structure-property relationships of crosslinked polymers but also give elastomers and gels with well-controlled mechanical properties such as elasticity, [9][10][11] mesh size, stretchability 1,2,10,12,13 and fracture toughness. 14 But due to the permanent nature of the crosslinks, these network do not exhibit any viscoelasticity.…”
Section: Introductionmentioning
confidence: 99%
“…1a). These ideal covalent polymer networks not only provide powerful tools to study structure-property relationships of crosslinked polymers but also give elastomers and gels with well-controlled mechanical properties such as elasticity, [9][10][11] mesh size, stretchability 1,2,10,12,13 and fracture toughness. 14 But due to the permanent nature of the crosslinks, these network do not exhibit any viscoelasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Hashimoto et al solved this problem by introducing “pH‐buffering IL” . As shown in Figure , they established a “pH‐buffering IL” by adding an imidazolium‐based protic IL (pIL; as a proton source) and its conjugated base to the solvent aprotic ionic liquid (aIL).…”
Section: Resultsmentioning
confidence: 99%
“…From a kinetic study, they also found that the gelation reaction undergoes a simple second‐order reaction of the two Tetra‐PEGs in the pH‐buffering IL. The gelation rate constant, k gel , of the ion‐gel system was 2 orders of magnitude smaller than that in the corresponding hydrogel system, which is ascribed to the difference in the activation entropy, ΔS‡, of the cross‐end coupling reactions . The reaction efficiency at the cross‐linking point was experimentally estimated to be 92% by spectroscopic measurements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Networked polymers have been used as indispensable materials for a wide range of applications, including adhesives, sealants, and coatings . The synthesis of networked polymers relies on two major strategies: crosslinking of linear polymers with reactive side chains, and polymerization of multifunctional monomers, that is, molecules bearing multiple reactive groups . In the latter strategy, not only appropriate choices of reactive groups, but also their numbers, locations, and the structures of the core part to which those reactive groups are attached, are essential factors in designing multifunctional monomers.…”
Section: Introductionmentioning
confidence: 99%